Development of Dorama card learning to improve critical thinking skills - Annisa Rohimah Hasri Hasibuan; Nirwana Anas (Universitas Pendidikan Indonesia, 2025)
Students have difficulty understanding Science learning due to a lack of attractiveness in learning. Therefore, this study aims to develop science learning media with Domino Rantai Makanan (Dorama) cards. The research used the Research and Development (RnD) method with the ADDIE development model. Data collection techniques include observation, interviews, questionnaires, (pre-test and post-test), and validation sheets from media and material experts. Data analysis was conducted using the N-gain test to measure the increased critical thinking. The results of media and material expert validation showed a very high level of validity. At the same time, the teacher's response proved that the Dorama card media was well received. Furthermore, the increase in students' critical thinking skills was significant. This research confirms that Dorama card learning media can encourage learning attractiveness. In addition, it provides student learning experiences in the form of connecting theory with practice through visualization and logical analysis, providing meaningful learning experiences and encouraging students to think critically by identifying cause-and-effect, testing hypotheses, and concluding grade V students of UPTD SDN 018452, Asahan, North Sumatra. Abstrak Peserta didik kesulitan memahami pembelajaran Ilmu Pengetahuan Alam (IPA) disebabkan kurangnya daya tarik dalam belajar. Maka dari itu, penelitian ini bertujuan untuk mengembangkan media pembelajaran IPA dengan kartu Domino Rantai Makanan (Dorama). Penelitian menggunakan metode Research and Development (RnD) dengan model pengembangan ADDIE. Teknik pengumpulan data meliputi observasi, wawancara, angket, (pre-test dan post-test), serta lembar validasi dari ahli media dan materi. Analisis data dilakukan menggunakan uji N-gain untuk mengukur peningkatan berpikir kritis. Hasil penelitian menunjukkan bahwa hasil validasi ahli media dan materi menunjukan hasil pada tingkat validitas yang sangat tinggi. Sedangkan Respons guru membuktikan bahwa media kartu Dorama diterima dengan baik. Selanjutnya peningkatan kemampuan berpikir kritis peserta didik terlihat signifikan. Penelitian ini menegaskan bahwa media pembelajaran kartu Dorama dapat mendorong daya tarik belajar. Selain itu, memberikan pengalaman belajar peserta didik dalam bentuk menghubungkan teori dengan praktik melalui visualisasi dan analisis logis, memberikan pengalaman belajar yang bermakna dan mendorong peserta didik untuk berpikir kritis dengan mengidentifikasi sebab-akibat, menguji hipotesis, dan menarik kesimpulan Pada peserta didik kelas V UPTD SDN 018452 Asahan, Sumatera Utara. Kata Kunci: berpikir kritis; kartu Dorama; pengembangan media ajar